Construction and characterization of yeast two-hybrid cDNA library derived from LFBK cell line. Issue 3 (May 2015) - Mahajan, Sonalika; Sharma, Gaurav Kumar; Matura, Rakesh; Subramaniam, Saravanan; Mohapatra, Jajati Keshari; Pattnaik, Bramhadev
Abstract The cDNA libraries are indispensable and critical tools for performing protein–protein interaction studies. In this study, a high quality yeast two-hybrid cDNA library from the LFBK cell line was constructed and characterized. LFBK cell line was originally derived from the swine kidney cells and is highly susceptible to foot-and-mouth disease virus (FMDV) infection. The total RNA was extracted from the LFBK cells and the switching mechanism at the 5′ end of RNA template (SMART) technique was employed for the cDNA synthesis. Subsequently, double stranded cDNA was amplified by long-distance PCR, purified and co-transformed with pGADT7-rec vector in yeast strain Y187. The quality parameters of the constructed library were evaluated to qualify the constructed library. Nucleotide sequencing of the randomly selected clones from the library confirmed the swine genotype of LFBK cell line. The LFBK cDNA library was mated with the 2C protein of FMDV in yeast two-hybrid (YTH) system and several putative interaction partners were identified in the preliminary screening. The LFBK library was observed to be of high quality and could potentially be applied to protein interaction studies between FMDV and the host cells using YTH system.